(untitled) (Research, Society and Development, 2020)
Corrosion is a global problem that has a great economic impact, due to direct and indirect costs, affecting developed and/or developing countries. Various methods are used in the industry to avoid and reduce the rate of deterioration of metallic materials. Corrosion inhibitors are added to corrosive media to mitigate the deterioration of the metal against solutions to which they are exposed; as is well known, they are organic compounds that contain in their molecular structure polar groups such as nitrogen, sulfur and/or oxygen atoms; heterocyclic compounds with polar functional groups and double bonds. To improve the anticorrosive process, new materials have been investigated experimentally and through theoretical calculations. The study of the corrosion mechanism and the action of corrosion inhibitors, as well as the factors that influence the effectiveness of the inhibition, has been the subject of numerous theoretical studies. Among them, studies based on density functional theory have received great attention. The aim of this article is to present a brief review of the use of theoretical calculations, focusing the Density Functional Theory (DFT) method as a tool in the analysis of the properties of organic molecules with possible applications as corrosion inhibitors. This review presents the most important electronic properties and reactivity indexes related to the efficiency of organic corrosion inhibitors such as: the energies of the frontier molecular orbitals and the energy of the gap (HOMO/LUMO), dipole moment, electronegativity, chemical potential, hardness, softness, fraction of electrons transferred, global electrophilicity index. In addition, local quantum chemical descriptors such as charge, Fukui function and softness has also been explored. As conclusion, it can be considered that DFT calculations provide strong evidence to complement experimental investigations or even to safely predict some experimentally unknown properties related to corrosion inhibitors.